2020
DOI: 10.1111/and.13899
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of carvacrol against diabetes‐induced reproductive damage in male rats: Modulation of Nrf2/HO‐1 signalling pathway and inhibition of Nf‐kB‐mediated testicular apoptosis and inflammation

Abstract: Diabetes mellitus (DM) is a metabolic disease which blood glucose level rises as a result of insufficient secretion of insulin hormone from the pancreas or failure to use the produced insulin hormone effectively. Hyperglycaemia significantly affects carbohydrate, lipid, protein metabolism and causing serious functional complications (Vlad & Popa, 2012). Treatment costs are quite high due to serious complications (Singh et al., 2013). Studies in recent years have shown that diabetes also has serious effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 109 publications
(164 reference statements)
0
7
0
Order By: Relevance
“…Some studies have demonstrated that baicalin relieved hypoxia‐induced apoptosis of H9c2 cardiomyocytes by activating the Nrf2 pathway (Yu et al., 2019), and that polydatin inhibited microglial apoptosis by enhancing Nrf2 signaling and improved locomotor performance in rats with spinal cord injury (Lv et al., 2019). Additionally, carvacrol treatment downregulated the expression levels of Bax and NF‐κB, and upregulated the expression levels of Bcl‐2 and Nrf2 in diabetes‐induced reproductive damage rats (Arkali et al., 2021). The above results suggest that NF‐κB and Nrf2 induced by astrocytes may be related to self‐apoptosis after myelin debris phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that baicalin relieved hypoxia‐induced apoptosis of H9c2 cardiomyocytes by activating the Nrf2 pathway (Yu et al., 2019), and that polydatin inhibited microglial apoptosis by enhancing Nrf2 signaling and improved locomotor performance in rats with spinal cord injury (Lv et al., 2019). Additionally, carvacrol treatment downregulated the expression levels of Bax and NF‐κB, and upregulated the expression levels of Bcl‐2 and Nrf2 in diabetes‐induced reproductive damage rats (Arkali et al., 2021). The above results suggest that NF‐κB and Nrf2 induced by astrocytes may be related to self‐apoptosis after myelin debris phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, Arkali et al [112] studied the protective effect of carvacrol, a phenolic monoterpene with antioxidant activity present in essential oils of aromatic plants, on diabetes-induced reproductive damage in male rats by evaluating the Nrf2/HO-1 pathway, NF-κB-mediated apoptosis and sperm parameters. They found that carvacrol significantly reduced MDA levels, Bax and NF-κB protein expression levels, and significantly increased Bcl-2, Nrf2/HO-1 levels and consequently GPx and CAT activities; this condition exerted a positive effect on sperm parameters.…”
Section: Compounds Targeting Nrf2 and Influencing Male Fertilitymentioning
confidence: 99%
“…Diabetes mellitus-induced autooxidation of glucose and production of superoxide, glycation of proteins and formation of advanced glycation end (AGE) products, polyol pathway activity, increased protein kinase C activity, and hexosamine pathway (9) are associated with testicular injuries and excessive cellular ROS related to its production (10). High levels of fatty acids with reduced antioxidant levels make mammalian spermatozoa vulnerable to oxidative damage.…”
Section: Male Fertilitymentioning
confidence: 99%